Burden of asthma by severity and exacerbation frequency among adult patients naive to biologic asthma therapy: A Finnish cohort study - Kankaanranta, Hannu; Viinanen, Arja; Klåvus, Anton; Lassenius, Mariann I.; Olsen, Helga Haugom; Nieminen, Kaisa; Lyly, Annina; Kauppi, Paula; Lehtimäki, Lauri (Elsevier BV, 2025)
Background
Understanding the disease burden and characteristics of asthmatic patients with frequent exacerbations is important for optimal disease management and outcomes. Asthma, and especially severe uncontrolled asthma, associates with an increased disease burden, but the comparison across asthma severity and exacerbation frequency is largely missing.
Objective
We sought to assess the association of asthma severity and exacerbation frequency with medication use, mortality, sick leaves, disability pensions, health care contacts, and comorbidities among Finnish patients with asthma.
Methods
National longitudinal retrospective data on adult patients naive to biologic asthma therapy were used to match patients on the basis of age, sex, and region across 4 subgroups (5525 patients in each) of nonsevere or severe asthma with infrequent or frequent exacerbations. The clinical characteristics, mortality rates, and morbidity across the subgroups were analyzed.
Results
Exacerbation frequency associated with an increased disease burden regardless of asthma severity. Comorbidities, health care contacts, sick leaves, and disability pensions cumulated in patients with frequent exacerbations, peaking with severe asthma. In patients with severe asthma and frequent exacerbations, the all-cause mortality rate ratio was 1.9-fold (P < .001) versus patients with nonsevere asthma and infrequent exacerbations. Patients with frequent exacerbations were also exposed to high cumulative corticosteroid doses.
Conclusions
Despite improved outcomes in asthma over the past decades, a substantial proportion of patients experience frequent exacerbations. These patients are multimorbid and at increased risk of mortality. Exacerbation frequency, rather than asthma severity, seems to be the main factor associated with an increased disease burden. Clinical awareness should be raised to improve the management and outcomes for these patients.